Oculocardiac Reflex and Autonomic Modulation in a Broad-Snouted Caiman (Caiman latirostris) - Rodrigues Marques, Ana Letícia; Marangoni, Marina; Mamguê, Vitor Eduardo; Takazono Lemes, Mel; Martínez, Oscar; Braz, Paulo Henrique; Champion, Tatiana (Acta Scientiae Veterinariae, 2025)
Background: The oculocardiac reflex (OCR) is a neurophysiological response mediated by the vagus nerve, triggering changes in heart rate and rhythm in response to pressure applied to the ocular globe. While well-documented in humans and other mammals, the OCR remains less explored in reptiles, particularly crocodilians. Given the rising interaction between wildlife and urban settings, understanding OCR in these species has become essential due to potential implications in veterinary and wildlife medicine. This case report aimed to investigate the OCR in a broad-snouted caiman rescued from an urban environment, providing insights into its autonomic responses under ocular compression. Case: A juvenile broad-snouted caiman, approximately 45 cm in length and weighing 0.8 kg, was rescued from an urban household in Capanema, Paraná, Brazil. The animal, found in a dehydrated and lethargic state far from its natural habitat, was transported to the Wildlife Animal Service at the veterinary hospital of the Federal University of Fronteira Sul (UFFS), Realeza campus, for evaluation and possible release. The animal underwent electrocardiogram (ECG) monitoring using an INcardio X® device (INpulse, Florianópolis, SC, BR) to assess changes in heart rate and rhythm during ocular pressure, simulating vagal stimulation. Surface cup electrodes coated with conducting gel were placed on the animal’s cranial and caudal limbs for ECG readings. Application of ocular pressure induced a notable OCR response, evidenced by a 47% decrease in heart rate, dropping from 34 bpm to 16 bpm, along with changes in heart rate variability (HRV) parameters and a 2nd-degree atrioventricular block. Three min after the release of ocular pressure, the heart rate returned to 29 bpm, with HRV values returning to baseline, indicating a recovery of autonomic balance. Discussion: Manual restraint in crocodilians often involves ocular pressure to facilitate temporary immobilization through vagal activation. However, the OCR poses substantial cardiovascular risks, as highlighted by this case. During OCR activation, HRV metrics such as Standard Deviation of NN intervals (SDNN) and Root Mean Square of Successive Differences (RMSSD) rose, reflecting increased heart rate variability likely due to heightened parasympathetic activity. Additionally, increases in the mean NN interval and the Cardiac Vagal Index (CVI) pointed to enhanced vagal modulation, while a drop in the Cardiac Sympathetic Index (CSI) indicated diminished sympathetic response. Changes in DFA parameters with increased α-1 and decreased α-2 values reflected short-term variability and reduced long-term complexity, respectively. These shifts underscored a significant autonomic imbalance dominated by parasympathetic tone. The atrioventricular block and multiple sinoatrial node depolarizations observed during the OCR response align with known reptilian cardiac responses to parasympathetic dominance. Similar findings have been reported in canine studies during OCR, suggesting that vagal modulation of HRV may share patterns across taxa. The results of this report underline the necessity of safety precaution for handling of crocodilians during ocular manipulation, as failure to recognize OCR could result in severe bradycardia, arrhythmias, or even cardiac arrest. Future studies should expand on the physiological implications of OCR in crocodilians, as insights from these investigations will be critical for veterinary practices involving these animals. This report provides pioneering data on HRV and OCR in a caiman, offering valuable perspectives for improving welfare and safety protocols in wildlife and veterinary care. Keywords: bradycardia, crocodilian, heart rate, heart rate variability, vago-vagal reflex.